Kinetic and Thermodynamic Adsorption of Cr(VI) onto Dried Oscillatoria Splendida in Aqueous Solution - Risfidian Mohadi; Doni Setiawan; Hilda Zulkifli (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
Kinetic and thermodynamic adsorption study of Cr(VI) ion in aqueous solutions by dried Oscillatoria Splendida biomass was investigated in the batch system. The Oscillatoria Splendida was isolated and cultured from algae swamp ecosystem in South Sumatera. The adsorption properties of Cr(VI) onto dried Oscillatoria Splendida biomass was studied by the influences of contact time, initial Cr(VI) ion concentration and temperature of reaction. The experimental results were the rate of adsorption followed the second-order kinetic model with the rate of reaction k2 is 0.00181 mg g-1 min-1 and the adsorption thermodynamic agree to the Langmuir’s model with amount of Cr(VI) removed from aqueous solution increased with increasing Cr(VI) concentration with the higher adsorption energy was 8.46 kJ/mol at 50 °C.